Solid modelling in a virtual reality environment - Zhong, Y.; Shirinzadeh, B.; Ma, W. (Springer Verlag, 2005)
This paper presents a constraint-based methodology for intuitive and precise solid modelling in a virtual reality (VR) environment. A hierarchically structured and constraint based data model is developed to support solid modelling in the VR environment. A constraint reasoning engine is also developed to automatically deduce allowable motions for precise constraint-based 3D manipulations. A prototype system of product modelling has been successfully developed, and experimental results demonstrate the advantage of precise solid modelling through constraint-based manipulation in virtual environments.